Explaining exchange rate anomalies in a model with Taylor-rule fundamentals and consistent expectations. (February 2017) - Lansing, Kevin J.; Ma, Jun
Highlights: We introduce boundedly-rational expectations into an asset-pricing model of the exchange rate. Agents augment a lagged-information random walk forecast with news about fundamentals. Model generates exchange rate behavior that is remarkably similar to that observed in the data. Abstract: We introduce boundedly-rational expectations into a standard asset-pricing model of the exchange rate, where cross-country interest rate differentials are governed by Taylor-type rules. Agents augment a lagged-information random walk forecast with a term that captures news about Taylor-rule fundamentals. The coefficient on fundamental news is pinned down using the moments of observable data such that the resulting forecast errors are close to white noise. The model generates volatility and persistence that is remarkably similar to that observed in monthly exchange rate data for Canada, Japan, and the U.K. Regressions performed on model-generated data can deliver the well-documented forward premium anomaly.